Utilização dos serviços de saúde por pessoas com Diabetes Mellitus tipo 2 - Buriol, Daniela (2021)
The use of health services due to type 2 Diabetes Mellitus (DM) and its complications is associated with people's needs, the provision of services, financial resources, health professionals, as well as socioeconomic and cultural conditions. The objective was to know the sociodemographic and clinical characteristics of people with type 2 DM attended in the Primary Health Care (PHC) of Santa Maria - RS and understand their perception about the use of health services in the municipal network. This is a quantitative-qualitative study. In the first stage, a quantitative research was carried out whose data source was a matrix project. In the second stage, a qualitative research was carried out through semi-structured interviews with people with self-reported type 2 DM who participated in the matrix project. Data analysis of the quantitative stage was carried out using descriptive and analytical statistics in the Statistical Package for the Social Sciences software. The qualitative stage was based on the Content Analysis proposed by Bardin. To carry out this research, ethical aspects related to research with human beings were followed. There was a predominance of white people (44–73.3%), males (32–53.3%), with low family income (32–53.3%), aged 40 to 49 years (18–30.0 %), with zero to eight years of education (38–63.3%). As for clinical characteristics, Hypertension predominated among 36 (60.0%) of respondents, followed by obesity in 35 (58.3%) of participants and dyslipidemia in 33 (55.0%) of them. A higher concentration of male type 2 DM people was identified in the Central-Urban (13–21.7%) and Midwest (12–20.0%) regions of the city. The Midwest registered a greater concentration of low-income people. In the West and Central-Urban regions, the association between hypertension and DM was found in ten people (16.7%) and nine (15.0%), respectively. In the qualitative stage, 15 people were interviewed, ten men and five women. An itinerary of the participants that passed through the PHC, outpatient and hospital service, was identified to monitor the DM and treat complications. They used the APS services as a gateway for diagnosis, renewal of prescriptions, verification of blood glucose levels, exams and consultations. The limitations of the city's health services, identified by the participants, were the renewal of prescription without clinical evaluation, flow of care through the distribution of tokens, little bond, insufficient interpersonal relationship and lack of reception by the PHC, in addition to a long waiting time for expert service, lack of public investment, and the Covid-19 pandemic. The strengths mentioned were good service and reception by the specialized outpatient service, hospital resoluteness and quality of all services. Most of the participants, who were being followed up at the specialized outpatient service, did not maintain follow-up and bond with the PHC reference service. It is concluded that knowing how people with type 2 DM use health services is essential to identify access barriers and guide health policies, providing equity of access and guidance in the design of policies aimed at reducing inequities in health.